The level of business ethics of small and medium-sized enterprises in the Visegrad group - Metzker, Zdenko; Belas, Jaroslav Jr.; Oodrejka, Roman; Dvorsky, Jan (Serbian Journal of Management, 2023)
The aim of the paper is to define and compare the significant attributes in the field of business ethics according to the size of the firm, gender and education of entrepreneurs in the SME segment in sum in the V4 countries. The empirical research, which was aimed at identifying the attitudes of small and medium-sized firms, was conducted in June 2022 in the Visegrad Four countries (Czech Republic, Slovakia, Poland and Hungary). The data collection was carried out by the external firm. Statistical hypotheses were tested through descriptive statistics, chi-square and Z-score at α = 5% significance level. The attitudes of SMEs towards the following statements were examined: ST1: I consider ethics in business important; ST2: I consider the ethical implications of my decisions when managing my business; ST3: I feel good when I behave ethically in business; and ST4: Our company enforces rules of ethical conduct in business. We find that the level of agreement with these statements is high. We did not find statistically significant differences in responses based on defined demographic characteristics.